INVESTIGATION OF CALCIUM- AND HYALURONIC ACID-CONTAINING DRUGS OSTEOPLASTIC ACTIVITY IN RATS WITH PERIODONTITIS - Larkina S.О.; Makarenko, O.A.; Vastyanov, R.S.; Yermuraki, P.P. (World of Medicine and Biology, 2020)
The aim of the research was to investigate the effect of subgingival injection of the solutions of calcium and hyaluronic acid on the condition of the bone tissue of the alveolar process of the lower jaws of rats with experimental periodontitis. The conducted experimental trials confirmed the intensification of the resorption processes in the jaw bone tissue of rats, which were fed peroxidized oil for a long time. Thus, the alimentary intake of lipid peroxides led to an increase in atrophy of the alveolar process of the lower jaw of rats and the loss of calcium in the bones of the jaws. Hydroxyapatite injections had a slight effect on the studied parameters, since the atrophy of the alveolar bone could not be slowed down, and the biochemical indicators, despite some improvements, did not reach normal values. Calcium in combination with unstabilized hyaluronic acid turned out to be much more effective. The authors insisted that further experimental trials are required in order to determine the frequency of subgingival calcium injections of calcium hydroxyapatite with non-stabilized hyaluronic acid.